A spatial testimony: The politics of do-it-yourself aerial photography in East Jerusalem. (June 2019) - Keysar, Hagit
In this paper, I examine the kind of testimony enabled by do-it-yourself aerial photography with kites or balloons in situations of political and spatial conflict, and how this plays on the surface of proliferating uses of geospatial technologies in a human rights context. The case study presented here concerns the use of do-it-yourself aerial photography in the context of discriminatory urban planning policies and practices against the Palestinian population of East Jerusalem. Its analysis shows that the political potentials of do-it-yourself aerial photography go further than just enabling the independent production of high-resolution aerial evidence in near real-time settings. It brings forth a distinctive kind of testimony, which I term a "spatial testimony, " that pushes against a certain threshold of participation in human rights truth production and sheds light on the political role embodiment may play in such processes. The "spatial testimony" denotes not only the visual image or the speech act related to the testimony but also the whole process of experimentation with a self-built instrument that unsettles and reconfigures the political space of relations between human rights, human bodies, and technoscientific objects.